Implementation of Augmented Reality in Learning to Know the Android-Based Solar System - Rahmad Ginanjar; Huda Faturrohim (Universitas Amikom Purwokerto, 2022)
The current learning media is very varied. The current social era requires students to really learn independently, including determining their learning patterns for future goals. According to the survey, currently, there are many students who are still unable to determine and make decisions about selecting further studies at tertiary institutions or jobs that are in accordance with their identity. Even though it is very important that teenagers are fertilized from the age of 13 to find out their interests. This application aims to determine youth interest in work with the website-based Rothwell Miller Inventory Blank method. RMIB (Rothwell Miller Inventory Blank) is a tool for measuring a person's interest based on a person's attitude towards a job with the development method, namely the waterfall which goes through several stages including system analysis, design, coding, testing, and maintenance. This application will rank 9 table indicators, namely from A-I and each table contains 12 job categories which will be sorted from the smallest number as the preferred job while the largest number is for the disliked job. In this study, the user conducts a test to determine interest in work according to his wishes, with one of the work outputs being mechanical.